Comparative Assessment of Asphalt Volatile Organic Compounds Emission from field to laboratory. (1st January 2021) - Li, Na; Jiang, Qi; Wang, Fusong; Cui, Peide; Xie, Jun; Li, Jiashuo; Wu, Shaopeng; Barbieri, Diego Maria
Abstract: The quantifying evaluations of asphalt volatile organic compounds (VOCs) throughout the road construction process are growing concerned since VOCs are widely recognized for its adverse effects on both human health and environmental issues. This paper made a comparison on VOCs emission assessment between actual construction field and laboratory simulation, aiming to verify their research gap at similar applied conditions. Atmospheric sampling pump and adsorption tube were used to record the VOCs samples from practical construction site, involving in hot asphalt storage tank, mixture plant, and paving site. Correspondingly, a sealed simulator for experimental VOCs collection was set-up in laboratory to investigate the VOCs amount released in different temperatures. Moreover, thermal desorption-gas chromatography-mass spectrometry (TD-GC-MS) was applied to analyze the detailed chemical composition and released quantification of VOCs samples. The results indicated that substance varieties and content in asphalt VOCs had considerable dependence on heating temperature. Both oxygen and thermality will trigger the increasing generation of hydrocarbon derivatives (HYD) in asphalt VOCs. For construction site, the investigated scenarios behaved great difference due to the complexity from on-site factors, however, approximating 74% of aliphatic hydrocarbons (ALH) tested in laboratory were fitted with the main components detected in construction site. Therefore, experimental simulation in laboratory could obtain a workable effect in signalling practical VOCs amount and compositions released in construction sites. This study provided a significant reference in connecting construction sites and laboratory research toward asphalt VOCs quantification. It laid down a basis for further total VOCs emission amount estimation and environmental effect assessment in the life-cycle of asphalt pavement construction, which is little concerned in corresponding research field.